2017
DOI: 10.5897/ajmr2017.8583
|View full text |Cite
|
Sign up to set email alerts
|

Community knowledge and attitudes on antibiotic use in Moshi Urban, Northern Tanzania: Findings from a cross sectional study

Abstract: There is increasing and spread of antibacterial resistance to antibiotics worldwide. The level of knowledge and attitudes of the community regarding the use of antibiotics in Tanzania is unknown. The present study identified determinants of knowledge and attitudes regarding antibiotics use in Moshi Urban district, Northern Tanzania. A cross-sectional study was conducted from April to June 2016 among community members whereby information was collected by using questionnaires on a sample of 292 randomly selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 23 publications
4
11
7
Order By: Relevance
“…The level of awareness observed in our study regarding antimicrobials and their use is similar to the ndings reported by studies in Nepal and Jordan [40,41]. The observed poor knowledge regarding AMU and AMR accords with the ndings reported previously [41,42]. The pattern observed in our study for knowledge of AMU and AMR to increase with an increased level of participants' education, contrasts with the ndings of previous studies elsewhere [41][42][43][44].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The level of awareness observed in our study regarding antimicrobials and their use is similar to the ndings reported by studies in Nepal and Jordan [40,41]. The observed poor knowledge regarding AMU and AMR accords with the ndings reported previously [41,42]. The pattern observed in our study for knowledge of AMU and AMR to increase with an increased level of participants' education, contrasts with the ndings of previous studies elsewhere [41][42][43][44].…”
Section: Discussionsupporting
confidence: 84%
“…In our study, we recorded a moderate attitude regarding the appropriate use of antimicrobial, which was a lower level than previously reported by other studies in Tanzania [42] and in Hong Kong [66]. However, the different scoring schemes used between our study and these other studies might have led to the different conclusions made regarding the attitude scores.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Poor knowledge about antibiotics may be a factor influencing prescribers' attitudes toward antibiotic use and prescription practices, which then becomes a problem for patients and the community. 8 Lack of confidence and training about the rational use of antibiotics among prescribers and dispensers is a serious problem, especially when antibiotics are prescribed in the absence of cause of illness, thus increasing the risk of antibiotic resistance and adverse reactions. [9][10][11] Several factors contribute to the inappropriate prescription of antibiotics, including a health care provider's knowledge and experiences, uncertain diagnosis, patient expectations, pharmaceutical marketing influences, and unregulated antibiotic dispensing.…”
Section: Introductionmentioning
confidence: 99%